math

posted by .

simplify

3sqrt-1/8

  • math -

    I am not certain what is the operand of the sqrt function.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  2. Algebra - sqrts

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  3. Math

    Simplify by factoring. ^3sqrt 54x^8
  4. Pre-Cal

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  5. Pre-Cal(Urgent)

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  6. Pre-Cal

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  7. Math(Please check)

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  8. math

    simplify 3sqrt-1/8
  9. Simplifying radical expressions

    how do you multiply and simplify 3*^3sqrt of 5y^3* 2* ^3sqrt of 50y^4
  10. Calculus

    1) yy'-e^x= 0, and y=4 when x=0 means that: A)y=x-lnx^2+4 B)y^2=4x^2+3 C)y=-2x+1/2x^3 D)y^2=2e^x+14 E)1/2ln|x^2+4|+6 2) The rate of change of P with respect to t is directly proportional to (10-t) and inversely proportional to the …

More Similar Questions